Benefits of the Screening Program for Colorectal cancer:: The lesions thus detected are less advanced than symptomatic - Montano, Daniel; Martínez, Luz; Fenocchi, Eduardo; Colet, Andrés; Rondán, Mariella; Bentancor, Marisel (Cirugía del Uruguay, 2005)
Colo-rectal Cancer is a serious health problem. miso ganglionar. Therefore we have developed a Screening program for detection and treatment of the disease at an Presentado a 51 º Congreso Uruguayo de Cirugía, Punta del Este, 1 al 4 de noviembre 2000 <1! Pro/ Adj. de, Clínica Quirúrgica "]" Residente de U.PRO.ME. <2! Practicante Interna <3! Médico Gastroenterólogo-Endocospista -Área Gastroenterológica de U.PRO.ME. !4! Médico Gastroenterólogo - Director Operativo Programa Cáncer Digestivo del MS.P. !5! Pro/ Adj. Clínica Quirúrgica "2" - Área de Cirugía de U.PRO.ME. 16! Pro/ Adj. de Anatomía Patológica - Área de Anatomía Patológica de U.PRO.ME. Correspondencia: Dr. Daniel Montano e-mail: dr.d.montano@adinet.com.uy early stage. Lesions thus detected are less advanced than in symptomatic cases A group of patients was diagnosed as carrying a Colo-Rectal Cancer through our Screening program and was compared with another group that was diagnosed on the basis of symptoms.